Mobile primary health care clinics for Indigenous populations in Australia, Canada, New Zealand and the United States: a scoping review protocol. Issue 5 (May 2020) - Beks, Hannah; Ewing, Geraldine; Muir, Rebecca; Charles, James; Paradies, Yin; Clark, Robyn; Versace, Vincent L.
ABSTRACT: Objective: The objective of this review is to explore and examine the available evidence on mobile primary health care clinics for Indigenous populations in Australia, Canada, New Zealand and the United States. Introduction: Despite the evidence for the effectiveness of primary health care in improving health outcomes, accessing primary care services is often problematic for Indigenous populations in Australia, Canada, New Zealand and the United States. Improving the accessibility of primary health care services for Indigenous populations is considered essential to alleviating the burden of disease and improving well-being. Inclusion criteria: The review will consider literature that discusses the implementation of a mobile primary health clinic for Indigenous populations. Mobile primary health care clinics targeting Indigenous populations of all ages will be included in this review. Transportable clinics (e.g. van, truck or bus) fitted with health care equipment that deliver health services in a defined geographical area will be included. Only literature published in English from 1 January 2006 will be included. Methods: Ovid MEDLINE, CINAHL, Embase, Cochrane Database of Systematic Reviews and SocINDEX will be searched, as well as gray literature sources. The full-text of selected literature will be retrieved and assessed in detail against the inclusion criteria by two independent reviewers. Data will be extracted by two independent reviewers, and a narrative summary will be provided on the objectives, concepts and results of the review question.